A Framework for Pilot Testing Health Risk Video Narratives. Issue 7 (6th June 2020) - Scherr, Courtney Lynam; Nam, Kelli; Augusto, Bianca; Kasting, Monica L.; Caldwell, Meghan; Lee, Marie Catherine; Meade, Cathy D.; Pal, Tuya; Quinn, Gwendolyn P.; Vadaparampil, Susan T.
ABSTRACT: Narrative messages may be superior to didactic messages when providing educational information due to their natural format for information sharing, ability to engage audiences, and engender positive thoughts about the message. Although narrative messages are gaining popularity in health promotion, little guidance exists regarding the development phase. Our team created a psychosocial narrative video intervention grounded in the Health Belief Model to increase breast cancer survivors' attendance at genetic counseling after treatment. Here we report the use of Learner Verification (LV) during an iterative video development process. Using LV, we conducted individual semi-structured interviews with patients and providers, after they viewed the video. Demographic information was analyzed using descriptive statistics, and verbatim interview transcripts were used to conduct a two-phase qualitative content analysis. Patient and provider participants ( n = 30) believed the video was attractive, relatable, and informative, and they identified areas for improvement including narrative coherence, changes to text and graphical information, and including more specific information. LV framework elicited audience feedback on the video intervention relevant to theoretical principles of narrative interventions, and highlighted audience preferences. In this study, LV interviews tapped into theoretical constructs of narratives and facilitated the iterative intervention design process.